Transcriptomics and metabolomics reveal tolerance new mechanism of rice roots to Al stress - Wang, Jingbo; Su, Chang; Cui, Zhibo; Huang, Lixiang; Gu, Shuang; Jiang, Sixu; Feng, Jing; Xu, Hai; Zhang, Wenzhong; Jiang, Linlin; Zhao, Minghui (Frontiers in genetics, 2023)
The prevalence of soluble aluminum (Al) ions is one of the major limitations to crop production worldwide on acid soils. Therefore, understanding the Al tolerance mechanism of rice and applying Al tolerance functional genes in sensitive plants can significantly improve Al stress resistance. In this study, transcriptomics and metabolomics analyses were performed to reveal the mechanism of Al tolerance differences between two rice landraces (Al-tolerant genotype Shibanzhan (KR) and Al-sensitive genotype Hekedanuo (MR) with different Al tolerance. The results showed that DEG related to phenylpropanoid biosynthesis was highly enriched in KR and MR after Al stress, indicating that phenylpropanoid biosynthesis may be closely related to Al tolerance. E1.11.1.7 (peroxidase) was the most significant enzyme of phenylpropanoid biosynthesis in KR and MR under Al stress and is regulated by multiple genes. We further identified that two candidate genes Os02g0770800 and Os06g0521900 may be involved in the regulation of Al tolerance in rice. Our results not only reveal the resistance mechanism of rice to Al stress to some extent, but also provide a useful reference for the molecular mechanism of different effects of Al poisoning on plants.